Rainfall–Runoff Processes and Modeling: The Case of Meja Watershed in the Upper Blue Nile Basin of Ethiopia. Landscape Dynamics, Soils and Hydrological Processes in Varied Climates - Berhane, S.; Zemadim, Birhanu; Melesse, A.M. (Springer, 2016)
Understanding the basic relationships among rainfall, runoff, soil moisture, and groundwater level are vital for effective and sustainable water resources planning and management. The current study was conducted to understand the dynamics of the hydrological processes and model rainfall–runoff relationship in Meja watershed in the Upper Blue Nile River Basin of Ethiopia. Meja watershed is part of the three research sites of the International Water Management Institute (IWMI) developed in early 2010. The study utilized primary data of soil moisture, shallow groundwater level, rainfall and runoff collected from the hydrological monitoring networks in the watershed. Hydrological models, Hydrologiska Byråns Vattenbalansavdelning (HBV) and Rainfall Runoff Library Soil Moisture Accounting and Routing (RRL SMAR), were configured to understand the relationship between rainfall and runoff in the watershed. Relationships among rainfall, runoff, soil moisture, and groundwater level were developed to understand the dynamics of hydrological processes in the watershed.